IMPROVING THE STUDENTS' READING SKILLS BY USING GAMES AT MTS NEGERI 1 DELI SERDANG - Fahdilla; Harahap, Anggie Nadia; Sulistia, Noni; Sy, T Zunita Miha; Asty, Rafadila; Deswinta, Risty; Putra, Surya Kelana (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
English is a very important language for used, apart from being popular, English is also used in various countries and regions. In learning English, many students use various ways to improve English skills, there are listening skills, speaking skills, writing skills and reading skills. In Improving and learning English is also a lot teachers and students who perform various techniques, methods and strategies to improve listening skills, speaking skills, reading skills and writing skills in English. But the results are obtained is not as expected, then the author conducts research on students with the theme of improvement students' reading ability by using games. With this game it will have an effect on increasing students' interest in reading, as well as students' enthusiasm in improving reading skills. This study used a qualitative approach with interview data collection techniques and the focus of the interviews was on students. The author's method use is to investigate how to improve students' reading skills in reading lessons, and also how the effectiveness of the game in skills reading students. The results of this study indicate that (1) students become more enthusiastic in English Subjects (2) students become more quickly know the new vocabulary (3) the student's memory is increasing (4) using games in learning is very effective to use.